Preliminary Treatment by Exogenous 24-Epibrassinolide Influences Burning-Induced Electrical Signals and Following Photosynthetic Responses in Pea (Pisum sativum L.) - Ekaterina Sukhova; Lyubov Yudina; Elizaveta Kozlova; Vladimir Sukhov (Plants)
Long-distance electrical signals (ESs) are an important mechanism of induction of systemic adaptive changes in plants under local action of stressors. ES-induced changes in photosynthesis and transpiration play a key role in these responses increasing plant tolerance to action of adverse factors. As a result, investigating ways of regulating electrical signaling and ES-induced physiological responses is a perspective problem of plant electrophysiology. The current work was devoted to the analysis of the influence of preliminary treatment (spraying) by exogenous 24-epibrassinolide (EBL) on burning-induced ESs and following photosynthetic and transpiratory responses in pea (Pisum sativum L.). It was shown that preliminary treatment by 1 µM EBL (1 day before the experiment) increased the amplitude of burning-induced ESs (variation potentials) in leaves and decreased the time of propagation of these signals from the stem to the leaf. The EBL treatment weakly influenced the magnitudes of burning-induced decreasing the photosynthetic linear electron flow and CO2 assimilation, but these changes were accelerated. Burning-induced changes in the cyclic electron flow around photosystem I were also affected by the EBL treatment. The influence of the EBL treatment on burning-induced changes in the stomatal water conductance was not observed. Our results show that preliminary treatment by EBL can be used for the modification of electrical signals and following photosynthetic responses in plants.